2010
DOI: 10.1111/j.1399-3038.2009.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the etiologies of chronic urticaria in children: A prospective study of 94 patients

Abstract: The etiologies of chronic urticaria (CU) in childhood remains incompletely understood because of limited data in children. The objective of this study was to examine some of the possible etiologies of CU in children by focusing on the functional autoantibody to FcepsilonRIalpha and IgE, thyroid autoimmunity, urticarial vasculitis, parasitic infestation and food allergy. Children 4-15 yr of age with CU were investigated for complete blood count, erythrocyte sedimentation rate (ESR), antinuclear antibody (ANA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
99
2
16

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(136 citation statements)
references
References 26 publications
19
99
2
16
Order By: Relevance
“…Jirapongsananuruk ve ark. 'nın 20 94 KÜ tanılı çocukta yaptığı çalışmada sadece 2 hastada ANA titresi 1/160 üzerinde saptanmış olup, <1/180 ANA titresinin sistemik lupus açısından %100 oranında negatif prediktif değere sahip olduğu McGhee ve ark. 21 tarafından ileri sürülmüştür.…”
Section: Discussionunclassified
“…Jirapongsananuruk ve ark. 'nın 20 94 KÜ tanılı çocukta yaptığı çalışmada sadece 2 hastada ANA titresi 1/160 üzerinde saptanmış olup, <1/180 ANA titresinin sistemik lupus açısından %100 oranında negatif prediktif değere sahip olduğu McGhee ve ark. 21 tarafından ileri sürülmüştür.…”
Section: Discussionunclassified
“…Brunetti et al (23) found no autoimmune diseases in any of 93 patients with chronic urticaria. In the other studies, the rate of increased anti-thyroid antibodies ranged between 1.1% and 4.3% (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…The success of specifying triggering factors in urticaria ranges between 21% and 83% in different studies (10)(11)(12)(13)(14)(15)(16). In our study, we found no factors that could lead to urticaria in approximately one fifth of the children with acute urticaria, and in approximately half of the children with chronic urticaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çocuklarda semptomatik dermatografizm, kolinerjik ürtiker, soğuk ürtikeri ve gecikmiş basınç ürtikeri en sık belirlenen fiziksel faktörler-dir. Aynı çocukta birden fazla fiziksel faktörün rol oynayabileceği akılda tutulmalıdır (20,21) .…”
Section: Etiyolojiunclassified